Digital Optimization In Improving Credibility Sharia Financing Institution - Ahmad Fauzi; Muhtadin Ridwan; Aunur Rofiq (Faculty of Law, Universitas Pekalongan, 2025)
This study aims to examine and explore the optimization of digitalization of financing institutions , where the development of digitalization optimization in transforming the financial sector and its impact, sharia compliance, and financial inclusion. Likewise , this research considers digital optimization​ in increasing credibility financing institutions . As a recommendation for further researchers to study more deeply the aspects that have not been reached, in the development of a sustainable digital economy . or an interdisciplinary approach to enrich the perspective on the topic discussed . The research method uses literature analysis, by looking at the current conditions related to digital economic transformation innovation , challenges and regulations, and its opportunities . The results of the study revealed that digitalization has great potential to accelerate access to Islamic finance for previously underserved communities. However, complex regulatory challenges and inadequate consumer education remain obstacles . Digital economic transformation services have provided easier and more affordable access for individuals and small and medium enterprises to use Islamic financial products and services. In addition, there needs to be cooperation between regulators, industry, and Islamic financial institutions to create a conducive environment for the growth of the Islamic economy . Therefore, the Islamic economy can continue to play its vital role in strengthening the Islamic financial sector and supporting broader finance .